Predispositions and challenges of agriculture from areas particularly facing natural or other specific constraints in Poland in the context of providing environmental public goods under EU policy - Marek Zieliński; Jan Jadczyszyn; Jolanta Sobierajewska (Agricultural Economics (AGRICECON), 2023)
The study's main objective is to determine the predisposition and challenges of agriculture to provide environmental public goods to society in areas particularly facing natural or other specific constraints (ANCs) established within their current delimitation in Poland. Its organisational features, economic situation, and the degree of interest in measures specifically serving the protection of the natural environment under the Common Agriculture Policy (CAP) EU were indicated. Statistically significant factors determined farmers' willingness to participate in these measures. It turned out that farms from ANCs communes with particularly difficult conditions significantly contribute to the total production potential of agriculture in Poland. However, compared to farms with better natural conditions, they are characterised by a lower income per 1 ha of utilised agriculture area (UAA) and a higher share of subsidies, including those for participation in environmental measures, which were implemented to a greater extent. Based on the logistic regression model, it was found that in ANCs communes with particularly difficult conditions, the most important factor of farmers' greater willingness to implement environmental measures was their higher level of education. On the other hand, this inclination was negatively affected by the higher income adjusted for operating subsidies per 1 ha of UAA.